(untitled) (European Journal of Pure and Applied Mathematics, 2025)
A new class of continuous multifunctions between an ideal topological space and a bitopological space, called upper (lower) weakly τ^β(σ_1,σ_2)-continuous multifunctions, has been defined and studied. Furthermore, several characterizations and some properties concerning upper weakly τ^β(σ_1,σ_2)-continuous multifunctions and lower weakly τ^β(σ_1,σ_2)-continuous multifunctions are discussed.